1978
DOI: 10.1073/pnas.75.5.2387
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of dual Ir gene-controlled T-lymphocyte proliferative response to poly (Glu56Lys35Phe9)n with anti-Ia antisera directed against products of either I-A or I-C subregion.

Abstract: Previous studies have demonstrated that both the antibody and T-lymphocyte proliferative immune responses to poly(Glu3Lys36Phe") (GL$) are under the control of two major histocompatibility-linked immune response (Ir) genes. One gene, termed lIrGLt-a, has been mappe to the IC or I-E subregion of the major histocompatibility complex, while the other, termed Ir-GL$-ft, has been mapped to the I-A subregion.In this paper we examine the effect of anti-I-region-associated (Ia) antisera on the T4ymphocyte proliferativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

1978
1978
1982
1982

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(17 citation statements)
references
References 13 publications
1
15
1
Order By: Relevance
“…Thus, genes in the I-A and I-E subregions control helper T cell induction, whereas genes in the I-J subregion control Ts3 induction. The functional role of I-A or I-E gene products in the presentation of antigen by macrophages or dendritic cells has been well documented (34,36). We hypothesize that I-J-encoded structures on antigen-presenting cells can serve a similar presentation function.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, genes in the I-A and I-E subregions control helper T cell induction, whereas genes in the I-J subregion control Ts3 induction. The functional role of I-A or I-E gene products in the presentation of antigen by macrophages or dendritic cells has been well documented (34,36). We hypothesize that I-J-encoded structures on antigen-presenting cells can serve a similar presentation function.…”
Section: Discussionmentioning
confidence: 99%
“…Schwartz et al [76] demonstrated that the proliferative response to GL~ could be blocked with anti-Ia sera specific for products of either of the I subregions which encode for the Ir-GL~ genes. Thus, the responses of B10.HTT and 9R T lymphocytes could be blocked by antisera directed against the I-E, I-C subregions (Table 16).…”
Section: The Association Between Ir and Iamentioning
confidence: 99%
“…Macrophages are required for the uptake and presentation of soluble protein antigens that precedes in vitro T-lymphocyte proliferation and T-and B-lymphocyte collaboration for an antibody response. Further, macrophage-lymphocyte interactions are regulated by the major histocompatibility complex (8)(9)(10)(11), specifically, by the Ia molecules on the sensitizing macrophages (12)(13)(14). Macrophage uptake and presentation is not limited to soluble protein antigens; it has recently been shown that radio-resistant splenic adherent cells (SACs) are required for the generation of cytotoxic T-lymphocyte (CTL) responses to both allogeneic membrane proteins (7) and trinitrophenyl-modified cells (6).…”
mentioning
confidence: 99%